Telling - In a Grove: From Short Story to Contemporary Performance - Saowarat, Thaveep; Phutthakhot, Pongsatorn; Jantarachairot, Witchuda; mokchai, Anugoon; Panyamongkol, Atchareeya; Kittikong, Tanatchaporn (Journal of Fine and Applied Arts Khon Kaen University, 2021)
Contemporary performance “Telling - In a Grove” is a practice as research in performing arts. The creative process involved an analysis and reflection in order to develop performance methodology. The project has two objectives; to create a contemporary performance “Telling - In a Grove” from the short story “In a grove” by Ryunosuke Akutagawa and to find out how to best manage this specific creative process. The artistic process devided into 3 steps: (1) Analyze and create script; (2) Experiment with forms and (3) Presentation a performance. The research frameworks including Postmodernism and Social Structure were embraced into creation of the performance with the message – we shall not judge others, as each one has his/her own reason within complex realities. In the part of production management, understanding the form of performance highly affects the communication process, especially to director’s direction and style and staff communication. As well as targeting group of audience and marketing design.